Whither policy innovation? Mapping conceptual engagement with public policy in energy transitions research. (July 2022) - Goyal, N.; Taeihagh, A.; Howlett, M.
Abstract: A transition to sustainable energy will require not only technological diffusion and behavioral change, but also policy innovation. While research on energy transitions has generated an extensive literature, the extent to which it has used the policy innovation perspective – entailing policy entrepreneurship or invention, policy diffusion, and policy success – remains unclear. This study analyzes over 8000 publications on energy transitions through a bibliometric review and computational text analysis to create an overview of the scholarship, map conceptual engagement with public policy, and identify the use of the policy innovation lens in the literature. We find that: (i) though the importance of public policy is frequently highlighted in the research, the public policy itself is analyzed only occasionally; (ii) studies focusing on public policy have primarily engaged with the concepts of policy mixes, policy change, and policy process; and (iii) the notions of policy entrepreneurship or invention, policy diffusion, and policy success are hardly employed to understand the sources, speed, spread, or successes of energy transitions. We conclude that the value of the policy innovation lens for energy transitions research remains untapped and propose avenues for scholars to harness this potential. Highlights: Energy transitions research can be clustered in 15 themes, public policy being one. Analytical or conceptual engagement with public policy is limited in the literature. The notions of policy mixes, policy change, and policy process used most frequently The policy innovation lens – invention, diffusion, or success – is rarely employed. We identify avenues for shedding light on policy innovation in energy transitions.